Computer self-efficacy, knowledge and use of technological pedagogical and content knowledge among faculty members pursuing post-graduate degree programs Charlene Elouise D. Guerrero. - Guerrero, Charlene Elouise D.; Erlyn A. Sana, PhD (Manila National Teacher Training Center for the Health Professions, 2018)
Technology has been a vital part of the 21st century classroom. The TPACK framework provides a structure on how to incorporate it effectively. In order to expertly do this, faculty members should be confident enough with their computer skills. This study focuses on the relationship between computer efficacy (CSE), knowledge, and use of TPACK. Among faculty members pursuing post-graduate degree programs, to the study: 1) determined the perceived levels of computer efficacy; 2) determined the perceived levels of TPACK; 3) described the use of TPACK as reflected in their actual instructional designs; 4) determined the correlation between computer self-efficacy, knowledge, and use of TPACK. This study was conducted in one government graduate school in Manila, Philippines. Forty-five faculty members were chosen as respondents using the following inclusion criteria: 1) currently enrolled in postgraduate programs; 2) currently teaching in their respective professional fields and 3) willing to provide a sample of their instructional design if available. The Computer Self-Efficacy Scale developed by Teoh and Koh in 2010 was used to assess CSE. TPACK was measured by administering the Survey of Preservice Teachers' Knowledge of Teaching and Technology by Schmidt et al in 2009. Coding and revised scoring rubric for the Instructional Design based on the Technology Application and Integration in Education scoring rubric by Matthew Constant (2015) were used for evaluating the instructional designs of the participants. Mean, standard deviation and SD were used (p=0.05) to describe the variables identified in the objectives. Results show that 1) faculty members almost strongly agree that their high self-efficacy in terms of Basic Computer Skills (BCS) but neutral in Media Related Skills (MRS), and Web-based Skills (WBS); 2) faculty members are observed to be neutral in having knowledge in Technology Knowledge (TK) but agree in other constructs of TPACK; 3) BCS are correlated with TK and CK; 4) MRS are correlated with TK and knowledge of TPACK; 5) WBS are correlated with TK, Pedagogical Content Knowledge (PCK) and TPACK; 6) overall computer self-efficacy are correlated with TK, Pedagogy Knowledge (PK), PCK, and TPACK; and 7) the correlation with computer self-efficacy and use of TPACK cannot be explored due to limitations of data gathered. It is recommended to perform more in-depth analysis on the instructional designs to obtain correlation between constructs. Proficiency of graduate students-faculty on web-based instructions were also recommended to be looked into.
Thesis (Master of Health Professions Education)--University of the Philippines Manila
Panel members: Erlyn A. Sana PhD, Chair/Adviser; Nemuel S. Fajutagana MD MHPEd, Reader-Critic; Members: Maria Lourdes Dorothy S. Salvacion, DMD MHPEd; Maria Elizabeth M. Grageda, PTRP MHPEd
Keywords: TPACK; Computer skills